2007
DOI: 10.1128/jb.01249-06
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Histidine in Cytochrome c Maturation Permease CcmB of Shewanella putrefaciens Is Required for Anaerobic Growth below a Threshold Standard Redox Potential

Abstract: . Genetic complementation and nucleotide sequence analyses indicated that the CCMB1 respiratory mutant phenotype was due to mutation of a conserved histidine residue (H108Y) in a protein that displayed high homology to Escherichia coli CcmB, the permease subunit of an ABC transporter involved in cytochrome c maturation. Although CCMB1 retained the ability to grow on electron acceptors with high E 0 , the cytochrome content of CCMB1 was <10% of that of the wild-type strain. Periplasmic extracts of CCMB1 contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
1
11
0
Order By: Relevance
“…The reasons for this finding are not clear, but it may be due to repression of the Psr system by residual (1 mM) S 4 O 6 2Ϫ remaining in the system. A similar growth pattern was recently reported for cytochrome c maturation (ccmB) mutants of S. putrefaciens 200 that are unable to reduce NO 2 Ϫ but retain NO 3 Ϫ reduction activity (11). The S. putrefaciens CCMB1 mutant (with an in-frame deletion of ccmB) stoichiometrically converts NO 3 Ϫ to NO 2 Ϫ but is unable to respire the produced NO 2 Ϫ , and growth halts.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The reasons for this finding are not clear, but it may be due to repression of the Psr system by residual (1 mM) S 4 O 6 2Ϫ remaining in the system. A similar growth pattern was recently reported for cytochrome c maturation (ccmB) mutants of S. putrefaciens 200 that are unable to reduce NO 2 Ϫ but retain NO 3 Ϫ reduction activity (11). The S. putrefaciens CCMB1 mutant (with an in-frame deletion of ccmB) stoichiometrically converts NO 3 Ϫ to NO 2 Ϫ but is unable to respire the produced NO 2 Ϫ , and growth halts.…”
Section: Discussionmentioning
confidence: 61%
“…The majority of studies of anaerobic respiration by S. oneidensis have focused on the mechanism of electron transport to transition metals and radionuclides, while the mechanism of electron transport to metalloids such as inorganic sulfur compounds remains poorly understood (8,11,14,46,56). Previous studies demonstrated that several members of the Shewanella genus couple the oxidation of organic matter (or hydrogen) to the dissimilatory reduction of S 0 , a process that does not require direct contact between the cell and the S 0 particle (41,47) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mn(III) reduction was monitored colorimetrically by filtering samples through a disposable nylon filter with a pore size of 0.22 m (Millex) and subsequently monitoring absorbance spectrophotometrically at 480 nm (31). Mn(IV) reduction was monitored by mixing samples at a 1:9 ratio with 2 mM benzidine in a 10% acetic acid solution and monitoring absorbance spectrophotometrically at 424 nm (7,14). Fe(III) reduction rates were determined by monitoring Fe(II) production over time via HCl extraction, followed by a Ferrozine colorimetric assay (35,58).…”
mentioning
confidence: 99%
“…Fe(III) reduction rates were determined by monitoring Fe(II) production over time via HCl extraction, followed by a Ferrozine colorimetric assay (35,58). Cell growth was monitored by direct cell counts of acridine orange-stained cells via epifluorescence microscopy (Carl Zeiss AxioImager Z1 microscope) (8,14).…”
mentioning
confidence: 99%